Functional tests as predictors of ankle instability six months after an acute lateral ankle sprain - Lumbroso, D. S.; Gottlieb, U.; Zimmerman, D. R.; Springer, S. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This study investigated whether functional tests performed in the acute-subacute phase after a lateral ankle sprain and demographic data are predictive of ongoing ankle instability. METHODS: Thirty-three subjects (mean age 23.6±3.6 years, 63.6% males) were tested within three weeks of injury using the Balance Error Scoring System (BESS) modified with a dual cognitive task, the single-leg drop landing task (SLDL) and the drop vertical jump task (DVJ). The Cumberland Ankle Instability Tool (CAIT) at six months and the occurrence of a new sprain during follow-up were used to define potential ankle instability. Associations between functional tests and demographic variables to ankle instability outcomes were measured with chi2, Mann-Whitney U Test, and logistic regressions. RESULTS: Twenty-one participants (63.6%) met the ankle instability criteria at six months from injury. Each extra point in the Modified-BESS Foam-Tandem sub-task increased the likelihood of ankle instability (OR=1.55, P=0.037). Unwillingness to perform SLDL increased the likelihood of ankle instability (OR=10.0, 95% CI: 1.1-91.9, RR=1.8, 95% CI: 1.1-2.8), as did non-dominant ankle sprain (OR=6.0, 95% CI: 1.2-29.4, RR=1.88, 95% CI: 1.03-3.4). These three outcomes explained between 33.6% to 45.9% of the variance and correctly classified 75.8% of cases (sensitivity, 85.7%; specificity, 58.3%; P=0.004). CONCLUSIONS: The variables studied may help identify individuals who have an increased potential to develop ankle instability and may be used in decision-making. Further studies should validate these findings with a larger and broader sample.